The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00497-009-0121-4
|View full text |Cite
|
Sign up to set email alerts
|

How to shape a cylinder: pollen tube as a model system for the generation of complex cellular geometry

Abstract: Expansive growth in plant cells is a formidable problem for biophysical studies, and the mechanical principles governing the generation of complex cellular geometries are still poorly understood. Pollen, the male gametophyte stage of the flowering plants, is an excellent model system for the investigation of the mechanics of complex growth processes. The initiation of pollen tube growth requires first of all, the spatially confined formation of a protuberance. This process must be controlled by the mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 73 publications
2
62
0
Order By: Relevance
“…These results are consistent with the theoretical model of action of the Pectin Methyl Esterases (PMEs) during pollen tube growth. 10,11 Indeed, variations in cell wall properties are likely to be related, at least in part, by the modulation of the level of methylesterification of HG. might be an important cue for guiding the tube cells within the female tissue, as suggested with lily.…”
Section: Cell Wall Polysaccharides In Pollen Tube and Pistilmentioning
confidence: 99%
“…These results are consistent with the theoretical model of action of the Pectin Methyl Esterases (PMEs) during pollen tube growth. 10,11 Indeed, variations in cell wall properties are likely to be related, at least in part, by the modulation of the level of methylesterification of HG. might be an important cue for guiding the tube cells within the female tissue, as suggested with lily.…”
Section: Cell Wall Polysaccharides In Pollen Tube and Pistilmentioning
confidence: 99%
“…[3][4][5][6][7][8] The relevance of this discussion is not limited to the case of the pollen tube, since the mechanical principles that govern this process apply to all walled cells including those of plant, fungal and bacterial origin. [9][10][11][12][13][14] In a recent modeling study, 15 we showed that if the physical properties of the cell wall are allowed to vary, experimental results are recovered for the correlation between the turgor and the growth rate of oscillatory pollen tubes. Specifically, turgor and growth rate are correlated for oscillatory growth with long growth cycles while they are uncorrelated for oscillatory growth with short growth cycles.…”
Section: Modeling Pollen Tube Growthmentioning
confidence: 99%
“…The precisely controlled spatial distribution of biochemical components in the pollen tube cell wall is crucial for shape generation and maintenance of this perfectly cylindrical cell (Geitmann and Parre, 2004;Aouar et al, 2010;Fayant et al, 2010;Geitmann, 2010). The pollen tube, therefore, represents an ideal model system to study the link between intracellular signaling, biochemistry, cell mechanical properties, and morphogenesis in plant cells.…”
mentioning
confidence: 99%